Evaluation of Histological Changes of Liver after Induced Toxity by Zinc Oxide Nanoparticles in Adult Albino Rat - Sahib, Ahmad Hassan (American Journal of Biomedicine and Pharmacy, 2025)
Oreview: Every year, large quantities of zinc oxide nanoparticles (ZnO-NPs) are produced. These particles are utilized extensively in numerous industrial products and are now also being used in medication delivery and bioimaging. Aim: The recent report set out towards explore the impact of ZnO-NPs, or zinc oxide nanoparticles on hepatic tissue in an effort to discuss and comprehend the harmfulness and possible danger of its usage in medicine and diagnosis. Materials and Methods: Seventy-eight healthy male albino excpermenta rats were treated with zinc oxide nanoparticles (ZnO-NPs) and exposed to doses of 50 or 100 µL of ZnO-NPs with particle sizes of 25, 50, and 75 nm over periods of 5 or 10 days. Results: Findings of the recent work demonstrated the potential toxicity of (ZnO-NPs) affecting hepatic tissues. The main characteristics associated with liver cells alterations were chronically dilated central veins, portal and lobular infiltration by chronically inflammatory cells, hydropic degeneration, cloudy expanding, and fatty degradation. Conclusions: In summary, the noticed alterations might indicate that ZnO nanoparticles (NPs) have damaged hepatocytes, making them unable to deal with accumulated wastes as a result of metabolic and structural abnormalities that NPs produce.The changes that occurred were proportional to size, particularly the smallest producing the greatest impacts, and they were linked to the duration of exposure to ZnO-NPs.